2021
DOI: 10.1186/s12889-021-11720-w
|View full text |Cite
|
Sign up to set email alerts
|

Low socioeconomic position is a risk factor for delay to treatment and mortality of testicular cancer patients in Hungary, a prospective study

Abstract: Background In Hungary, the mortality rate for testicular germ cell cancer (TGCC) is 0,9/100000 which is significantly higher than the EU average. We prospectively evaluated the effect of socioeconomic position on patient delay and therapy outcomes. Methods Questionnaires on subjective social status (MacArthur Subjective Status Scale), objective socioeconomic position (wealth, education, and housing data), and on patient’s delay were completed by ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…A recent study conducted in the U.S. showed that the perceived lifetime risk of pancreatic cancer was significantly higher among people with high school education compared to those with lower educational attainment, leading to a higher chance of cancer detection (17). A recent Hungarian study identified education level as one of the most relevant factors leading to delays in the recognition of testicular cancer-related symptoms and found better survival rates among patients with higher levels of education (18). In a robust Danish study, the risk of advanced-stage lung cancer was lower in people with higher education levels, but higher in people living alone.…”
Section: Kiss Et Almentioning
confidence: 99%
“…A recent study conducted in the U.S. showed that the perceived lifetime risk of pancreatic cancer was significantly higher among people with high school education compared to those with lower educational attainment, leading to a higher chance of cancer detection (17). A recent Hungarian study identified education level as one of the most relevant factors leading to delays in the recognition of testicular cancer-related symptoms and found better survival rates among patients with higher levels of education (18). In a robust Danish study, the risk of advanced-stage lung cancer was lower in people with higher education levels, but higher in people living alone.…”
Section: Kiss Et Almentioning
confidence: 99%
“…19 Their findings corresponded to another Hungarian group in which a parent’s education level was associated with patient delay. 20 However, while the lower social quartile was associated with higher mortality, it was not related to more advanced stages. There was no direct evidence regarding one’s socioeconomic association being a factor in our series.…”
Section: Discussionmentioning
confidence: 95%
“…A larger study, including male respondents with more variable sociodemographic backgrounds, would allow us to verify the findings presented herein and perhaps identify some additional factors contributing to the delayed diagnosis of testicular cancer. Second, we retrospectively analyzed available data included in the survey and hence were unable to consider some other well-known determinants of diagnostic delay in cancer patients, such as economic status [ 4 , 21 ]. Third, analyzing the outcomes, we relied on the respondents’ subjective declarations instead of verifying their cancer awareness and psychological disposition with validated instruments.…”
Section: Discussionmentioning
confidence: 99%
“…However, still little is known about the causes of diagnostic delay in men with testicular malignancies. Some authors pointed to poor socioeconomic status as an obstacle in seeking medical advice early [ 20 , 21 ], but this explanation is not necessarily applicable to men from developed countries having unrestricted access to healthcare resources.…”
Section: Introductionmentioning
confidence: 99%